Tecnologia assistiva e computacional : contribuições para o atendimento educacional especializado e desafios na formação de professores - Caldas, Wagner Kirmse (2015)
In this study, we analyzed aspects related to how computer technology is utilized in the Educational Service Specialist (ESS) and how was the teacher training to use these features.. For this, we delimit the following specific objectives: to investigate the use of assistive technology (AT) computational in the context of multifunction resource room (MRR); discuss tensions, difficulties and possibilities related to the AT with an emphasis on computer technology for the ESS; analyze the formation of special education teacher for ESS having as recourse the AT with emphasis on computer technology, in order to mediate the learning process. The theoretical basis of this work was the historical-cultural approach, with reference to studies of Vygotsky and his collaborators. It is a qualitative research that made use of different methodological tools as focus groups, online questionnaire and the semistructured interview. To develop it, we conducted the data collection in different contexts, starting with the focus group's of inaugural research Oneesp, who served as a device to this research, followed by the application of a questionnaire to teachers participating research-training developed as an expansion in Espirito Santo state of inaugural research Oneesp by members of the Oeeesp and application in loco of semi-structured interviews with special education teachers, of the one MRR type II. Eighty-nine participants were teachers in Oneesp research, thirty teachers in research-training Oeeesp and two teachers for application of semi-structured interview in loco, respectively. These two teachers participated both Oneesp the research as the Oeeesp research. We analyze these three moments, from which emerged the appointments which provided us think, based on oral and written narratives of teachers: their formation to use the computational AT; their understanding of their formation for this purpose; their desire for a more targeted formation; the way they use technology in the resource room; their understanding of the difficulties and possibilities related to AT with emphasis on computer technology for the ESS. After this analysis, we concluded that few teachers who work in the MRR had a formation that would enable the application of computer technologies in their pedagogical mediation, combining theory and practice, with moments of training to privilege the presence times and in laboratories where they can interact with computers and their symbolic tools. Without this familiarity with the computational resources, teachers end up feeling insecure to use them, failing to enhance, by means of these features, the teaching-learning processes of students with disabilities. An investment is necessary in this type of formation and, more than that, which makes possible for teachers who work or intend to work in MRR. From an appropriate formation can enable teachers to use computing resources as mediators of the teaching-learning process of their students.